2015
DOI: 10.1186/s12885-015-2034-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer (NK) cells inhibit systemic metastasis of glioblastoma cells and have therapeutic effects against glioblastomas in the brain

Abstract: BackgroundGlioblastoma multiforme (GBM) is characterized by extensive local invasion, which is in contrast with extremely rare systemic metastasis of GBM. Molecular mechanisms inhibiting systemic metastasis of GBM would be a novel therapeutic candidate for GBM in the brain.MethodsPatient-derived GBM cells were primarily cultured from surgical samples of GBM patients and were inoculated into the brains of immune deficient BALB/c-nude or NOD-SCID IL2Rgammanull (NSG) mice. Human NK cells were isolated from periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 56 publications
0
59
0
Order By: Relevance
“…Natural killer (NK) cells are innate immune lymphocytes that destroy infecting or transformed cells without the need for activation, in contrast to T and B cells [1][2][3]. They have been the focus of more than 150 cellular-based immunotherapy clinical trials as of March 2017 (clinicaltrials.gov).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural killer (NK) cells are innate immune lymphocytes that destroy infecting or transformed cells without the need for activation, in contrast to T and B cells [1][2][3]. They have been the focus of more than 150 cellular-based immunotherapy clinical trials as of March 2017 (clinicaltrials.gov).…”
Section: Introductionmentioning
confidence: 99%
“…They have been the focus of more than 150 cellular-based immunotherapy clinical trials as of March 2017 (clinicaltrials.gov). The antitumour behaviour of NK cells has been harnessed to treat hematologic malignancies that include acute myeloid leukaemia, acute lymphoblastic leukaemia multiple myelomas [4], solid tumours such as melanoma [5,6], breast cancer [7,8], thyroid cancer [2] and glioblastoma [1,9]. Because of the low number of NK cells in peripheral or cord blood, immune cell therapy with NK cells requires an ex vivo expansion process to achieve relevant numbers that express activation markers, natural cytotoxicity receptors (natural-killer group 2, member D [NKG2D], NKp44, Fas ligand [FasL], etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In addition to blocking EGFR, Cetuximab also develops anti-tumour effects by provoking ADCC and inhibiting angiogenesis in vivo. [38][39][40] Therefore, the anti-proliferative activity of Cetuximab in vivo is stronger than that in vitro. Moreover, the AZ304 and Cetuximab combination showed a more obvious inhibition of the PI3K/AKT/mTOR and SRC/STAT3 pathway in both BRAF wild type and mutant CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Lee et al20 showed that GBM could form metastases in immune-deficient mice, but only when both adaptive and innate immune systems were inactive. This study also demonstrated the ability of the innate and adaptive immune systems to detect and destroy GBM tumor cells after they have crossed the blood–brain barrier and had invaded other systems – notably subcutaneous and lung tissue 20. The CNS lies behind the blood–brain barrier, in an immune-privileged site.…”
Section: Introductionmentioning
confidence: 99%
“…The CNS lies behind the blood–brain barrier, in an immune-privileged site. This protection is thought to allow the rapid growth associated with GBM; however, increasing numbers of studies demonstrate that the protection that this barrier provides is not absolute, and that cells of the immune system may permeate under specific circumstances 20. When GBM typically arises, the small number of antigen-presenting cells that could potentially detect the tumor and illicit an immune response (as seen outside the CNS) are inhibited by the expression of high levels of MHC class I (HLA-ABC) molecules on GBM tumor cell surfaces.…”
Section: Introductionmentioning
confidence: 99%